The Guardian of Ideology and the Pancasila by the Constitutional Court Decision - Hermanto, Bagus; Mas Aryani, Nyoman (Literasi Hukum, 2023)
The Constitutional Court also fulfils its role as guardian of ideology as a judicial institution with special authority. This has been attempted through a number of Constitutional Court decisions that have been the basis for the positioning and repositioning of Pancasila in its proper state. In particular, this paper investigates, reviews and analyses the role of the Constitutional Court as the guardian of ideology, the practice of various Constitutional Court decisions that reflect efforts as the custodian of ideology, as well as the attitude or direction of the Constitutional Court in maintaining the spirit of Pancasila in relation to the role of custodian of ideology. This paper shows that through its role in re-establishing the inseparable relationship between Pancasila and the 1945 Constitution, which is the basis for resolving constitutional cases, the Constitutional Court has endeavoured to uphold Pancasila. Nevertheless, critics argue that the use of Pancasila as a touchstone has led to legal uncertainty, and that elements of the state apparatus still make historical mistakes in the placement of Pancasila.